PENGARUH AUDIT TENURE, ROTASI AUDIT DAN REPUTASI KAP TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2017) - Pertamy, Ratu Ajeng Fahmiaty; Lestari, Tri (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This study aims to determine the effect of audit tenure, audit rotation and reputation KAP on manufacturing companies in the consumer goods industry sector listed on yhe Indonesia Stock Exchange 2015-2017. The research method used is descriptive verification. The data collection techniques used documentation study. The document covers the financial statements and annual reports of manufacturing companies in the consumer goods industry for the period 2015-2017 listed on the Indonesia Stock Exchange. Data processing in his research use statistic tes of regression of panel data with Random Effect Model.Based on statistical testing with the help of Eviews 8 software that audit tenure and audit rotation have a negative effect on audit quality, and tenure has positive effect on audit quality. The implication of this research is that company must improve audit quality by choosing affiliated KAP and routinely rotation, thereby minimizing risk caused by mistake of opinion in auditing process.Keyword: Audit Tenure, Audit Rotation, Reputation Kap and Audit Quality